Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009477
|View full text |Cite
|
Sign up to set email alerts
|

Wearable sensing for rehabilitation after stroke: Bimanual jerk asymmetry encodes unique information about the variability of upper extremity recovery

Abstract: Wearable sensing is a new tool for quantifying upper extremity (UE) rehabilitation after stroke. However, it is unclear whether it provides information beyond what is available through standard clinical assessments. To investigate this question, people with a chronic stroke (n=9) wore accelerometers on both wrists for 9 hours on a single day during their daily activities. We used principal components analysis (PCA) to characterize how novel kinematic measures of jerk and acceleration asymmetry, along with conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…Table 1 provides a summary of variables. In addition, two newly proposed variables were calculated, the jerk asymmetry index [34] and the spectral arc length [35,36]. These variables were calculated as they have been proposed to measure smoothness of movement, an aspect of quality of movement, by others in the field.…”
Section: Accelerometer Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 provides a summary of variables. In addition, two newly proposed variables were calculated, the jerk asymmetry index [34] and the spectral arc length [35,36]. These variables were calculated as they have been proposed to measure smoothness of movement, an aspect of quality of movement, by others in the field.…”
Section: Accelerometer Variablesmentioning
confidence: 99%
“…Two variables have been proposed to reflect movement smoothness as an aspect of quality of movement [34][35][36]. Figure 4 shows the relationship of the compensatory movement score to the jerk asymmetry index (Fig.…”
Section: Relationships Of Variables To Compensatory Movementmentioning
confidence: 99%
“…Like the use ratio, the mean of magnitude ratio values, compiled across a day or more also has a narrow distribution, with a mean of −0.1 ± 0.3. 21 Other examples of symmetry variables under development include jerk asymmetry and acceleration magnitude asymmetry, 26 percentage of contribution of each arm, 27 and variation ratio. 19 Early data from these more complex symmetry variables suggest that, like the use ratio, they will have a narrow range of distribution in the typical adult population.…”
Section: Variables Of Symmetry In Adultsmentioning
confidence: 99%
“…The dotted grey lines represent the range of JR50 values across the TD cohort kinematic metrics and existing functional tests. Using principal component analysis to identify the most indicative metric of human motion, they concluded that metrics based on acceleration and jerk contributed to the second principal component and accounted for 31% of variance across nine adult stroke survivors [22]. However, this work relied on an IMU, including both accelerometer and gyroscope, which increases sensor cost and decreases battery life.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 1985, Flash & Hogan described the coordination of arm movements with jerk, noting its advantage of capturing smoothness of movement [20], which is also commonly altered after neurologic injury [21]. Lucena and colleagues in 2017 showed the potential benefits of using jerk measured from inertial measurement units (IMUs) to evaluate bimanual arm use among stroke survivors [22]. They showed strong correlation with activity count measures; however, an IMU requires significantly more power, data storage, and cost than an accelerometer alone.…”
Section: Introductionmentioning
confidence: 99%